2008
DOI: 10.1097/sap.0b013e318141f742
|View full text |Cite
|
Sign up to set email alerts
|

Simplified and Versatile Use of Gluteal Perforator Flaps for Pressure Sores

Abstract: As a first choice for treating pressure sores, we present our experiences with gluteal perforator flaps and a simplified surgical technique. Twenty-three gluteal perforator flaps were used in 20 patients (13 males, 7 females; aged, 8-68 years) with pressure sores. The pressure sores were sacral in 16 patients, ischial in 2, and trochanteric in 2 patients. During follow-up, recurrence in the same region did not occur. Our simplified operative technique includes finding a suitable perforator with a Doppler probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Some authors have claimed that perforator flaps cannot be routinely used under certain circumstances. 8,9 However, our modifications of the perforator flap including beveled elevation of fat tissues or deepithelization of the distal flap can provide bulkiness and robustness equivalent to that of a conventional musculocutaneous flap. Our results also indicate that TFL-PBIF can also prevent intractable infection after complete debridement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors have claimed that perforator flaps cannot be routinely used under certain circumstances. 8,9 However, our modifications of the perforator flap including beveled elevation of fat tissues or deepithelization of the distal flap can provide bulkiness and robustness equivalent to that of a conventional musculocutaneous flap. Our results also indicate that TFL-PBIF can also prevent intractable infection after complete debridement.…”
Section: Discussionmentioning
confidence: 98%
“…7Y9 Although perforator flaps have considerable advantages including the possibility of creating large flaps and the ability to reuse the flap for recurrent sores, they are also associated with a number of drawbacks such as the need for meticulous dissection of the pedicle and the risk of compressing the vascular pedicle in paraplegic or quadriplegic patients who have difficulty in changing their position frequently. 8,9 To overcome these disadvantages, the ''perforator-based flap'' concept was introduced. 10,11 Flap elevation is stopped at the level of the perforators, and there is no need of further dissection to find proximal source vessels or time-consuming transmuscular dissection.…”
mentioning
confidence: 99%
“…Thus, the advantage of perforator-based flaps and V-Y flaps were combined as stated by Yildirim et al [27]. In the presence of various vascular sources (inferior and superior gluteal, pudental, lumbal, and lateral sacral arteries) freestyle local perforator-based flaps can be planned anywhere on the gluteal region, where Doppler signals of a sizable perforator vessel are determined [28]. Still, the best treatment remains to be prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Especially freestyle perforator-based fasciocutaneous flaps which include refined techniques of flap surgery take the advantage of less donor site morbidity [14]. Previously, gluteal perforator-based flaps were used to cover pressure sores on the gluteal region, to increase flap mobility for better aesthetic shape without tissue foldings and dog ears [25][26][27][28]. In the present study, the gluteal flaps were harvested based on one perforator in a V-Y fashion for closure of the gluteal upper quadrant defects caused by NS for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…2-7 Moreover, varying rates of total or partial failure for pedicled perforator flaps have been reported in clinical practice. 8,9 Little is known about the actual prevention of perfusion-related complications in perforator flaps through the use of hemodilution and its consequent effect on flap microcirculation. Only extremely controversial results and opinions concerning the effect of decreased hematocrit Background: Several studies showed the detrimental effect of pedicle torsion on flap survival; however, the impact of hemodilution in this peculiar condition has never been investigated.…”
mentioning
confidence: 99%